2022
DOI: 10.1021/acsomega.2c06048
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Fluoride Determination Using St. John’s Wort Extract as a Green Chromogenic Complexant for Al(III)

Abstract: In this study, we applied an innovative approach of green analytical chemistry to develop a novel and eco-friendly chromogenic agent for fluoride determination by making use of the nontoxic Al(III)-flavonoid complex in a natural extract from St. John’s wort plant. The initial intensely yellow-colored Al(III)-flavonoid complex formed in the plant extract was converted to a colorless AlF6 3– complex with increasing amounts of fluoride, and color bleaching of the Al-flavonoid chromophore (measured as absorbance d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…It also causes anorexia, gastroenteritis, weakness of muscles, muscle stiffness, dyspnea, sweating, and tachycardia. 4 The conventional methods used for the determination of Al 3+ and F − ions are spectrophotometry, 5,6 spectro-uorimetry, 5,7 and atomic absorption spectrometry. 8,9 Some of these methods suffer from low sensitivity and the need for preconcentration steps.…”
Section: Introductionmentioning
confidence: 99%
“…It also causes anorexia, gastroenteritis, weakness of muscles, muscle stiffness, dyspnea, sweating, and tachycardia. 4 The conventional methods used for the determination of Al 3+ and F − ions are spectrophotometry, 5,6 spectro-uorimetry, 5,7 and atomic absorption spectrometry. 8,9 Some of these methods suffer from low sensitivity and the need for preconcentration steps.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the sensor's detection limit for F − ions was as low as 0.5 ppm, which is substantially lower than the maximum allowable standard limit for fluoride 51 and comparable to recently reported colorimetric and fluorescence based sensors. 52,53 For varying concentrations (0–20 ppm) of F − ions, the relative change in fluorescence intensity ( F / F 0 , where F and F 0 are the fluorescence intensities of the nanocomposite complex in the presence and absence of F − ions) exhibits a linear relationship (Fig. 7(c)), where Y is the relative fluorescence intensity and X is the F − ion concentration (in ppm).…”
Section: Resultsmentioning
confidence: 99%
“…Green chemistry as a concept was first introduced in 1991 by PT Anastas when he launched a unique program in order to implement sustainable development in the area of chemical technology (7). Green chemistry has 12 principles which serve as guidelines for designing chemical products and methods (8,9) that reduce or occasionally remove the application and generation of harmful and hazardous chemical materials altogether by using solvents and chemicals that are entirely non-toxic to human health as well the immediate environment in order to design and create effective and non-hazardous methods facilitating the use of renewable solvents known as' new generation solvents' or 'solvents of the future' (10). Gu and Jerome proposed the first requirements for a solvent and a process to be considered green based on their availability, biodegradability, flammability, grade, performance, price, recyclability, renewability, stability, storage, toxicity, and synthesis (11).…”
Section: Introductionmentioning
confidence: 99%